Students Metacognitive Knowledge in Numeracy Literacy on Flat Surface Shapes Material - Nur Syafa Hatuwe; Christina Martha Laamena; Theresia Laurens (FKIP Universitas Lampung, 2024)
Students Metacognitive Knowledge in Numeracy Literacy on Flat Surface Shapes Material. Objectives: This research aims to describe the metacognitive knowledge of class VIII students in solving numeracy literacy problems on flat-sided geometric material. Methods: This type of research is qualitative research with 3 students as subjects selected based on test results (each representing high, medium and low abilities), as well as the teacher's consideration that the students are able to communicate well. The data analysis technique used consists of data reduction, data presentation, and drawing conclusions. Findings: The research results show that subjects with high metacognitive knowledge fulfill all indicators of strategy knowledge, knowledge of cognitive tasks and self-knowledge well. Subjects with moderate metacognitive knowledge only met each of the two indicators of strategy knowledge, knowledge of cognitive tasks; as well as self-knowledge. Subjects with low metacognitive knowledge did not meet the indicators of strategy knowledge, 2 indicators of knowledge about cognitive tasks, and 2 indicators of self-knowledge. Another finding is that metacognitive knowledge must be supported by meaningful repetition in terms of clearly identifying problem information and knowing how to solve it. The use of image representation in spatial building materials is necessary in solving problems. Awareness that an error has occurred in the solution must be followed by knowledge of how to correct the error. Conclusion: Metacognitive knowledge is very necessary for students to solve numeracy literacy questions. This knowledge must be followed by good and correct representational skills and procedural knowledge. Keywords: flat-side shape; numeracy literacy, metacognitive knowledge. DOI: http://dx.doi.org/10.23960/jpp.v14.i2.202460